2007
DOI: 10.1107/s1600536807054621
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bonding patterns in 2-amino-4,6-dimethoxypyrimidinium salicylate

Abstract: The asymmetric unit of the title compound, C6H10N3O2+·C7H5O3−, contains one 2‐amino‐4,6‐dimethoxypyrimidinium cation and a salicylate anion. The 2‐amino‐4,6‐dimethoxypyrimidinium cation interacts with the carboxylate group of the salicylate anion through a pair of nearly parallel N—H...O hydrogen bonds, forming an R22(8) ring motif. These motifs are centrosymmetrically paired via N—H...O hydrogen bonds, forming a complementary DDAA array. The typical intramolecular O—H...O hydrogen bond is observed in the anio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
3
16
0
Order By: Relevance
“…dihedral angles between the ring and the carboxylate group are 9.8 (4) and 21 (2) , respectively, with a dihedral angle between the two ring orientations of only 3(2) . A similar pattern of hydrogen-bonded rings is found in the structure of 2-amino-4,6-dimethoxypyrimidinium 2-hydroxybenzoate, (IV) (Thanigaimani et al, 2007), but a pair of S(6) rings is also present flanking the three central rings; the bond lengths in the cation again provide evidence for o-quinonoid-type bond fixation. Finally, we note that structures have been reported for a number of salts containing simpler substituted pyrimidines (Ebenezer et al, 2011;Ebenezer & Muthiah, 2012), as have those of some salts of substituted adenines (Tamilselvi & Muthiah, 2011;Karthikeyan et al, 2015).…”
Section: Figuresupporting
confidence: 64%
“…dihedral angles between the ring and the carboxylate group are 9.8 (4) and 21 (2) , respectively, with a dihedral angle between the two ring orientations of only 3(2) . A similar pattern of hydrogen-bonded rings is found in the structure of 2-amino-4,6-dimethoxypyrimidinium 2-hydroxybenzoate, (IV) (Thanigaimani et al, 2007), but a pair of S(6) rings is also present flanking the three central rings; the bond lengths in the cation again provide evidence for o-quinonoid-type bond fixation. Finally, we note that structures have been reported for a number of salts containing simpler substituted pyrimidines (Ebenezer et al, 2011;Ebenezer & Muthiah, 2012), as have those of some salts of substituted adenines (Tamilselvi & Muthiah, 2011;Karthikeyan et al, 2015).…”
Section: Figuresupporting
confidence: 64%
“…R 2 2 (8), R 2 4 (8) and R 2 2 (8). This type of DDAA array has also been observed in some TMP salts (Robert et al, 2001;Umadevi et al, 2002;Raj et al, 2003;Subashini et al, 2007;Thanigaimani et al, 2007). The DDAA array involves two TMP cations and two DTPC anions, generating a four-molecule aggregate.…”
Section: Compoundmentioning
confidence: 56%
“…Hydrogenbonding patterns in aminopyrimidine-carboxylate salts have been recently reviewed (Schwalbe & Cody, 2006). The crystal structures of 2-amino-4,6-dimethoxypyrimidinium 4-hydroxybenzoate monohydrate (Thanigaimani et al, 2007a) and 2-amino-4,6-dimethoxypyrimidinium salicylate (Thanigaimani et al, 2007b) have been reported by us. The present study was undertaken to obtain more information regarding patterns of hydrogen bonds in these types of compounds.…”
Section: Figurementioning
confidence: 96%